Features of endodontic treatment of teeth in a patient with arterial hypertension and hypersympathicotonia (LLC "Endo Press", 2020)
Patients with arterial hypertension deserve special attention, as they are more susceptible to anxiety before the treatment, so during the painful manipulations with the use of local anesthesia, the importance of evaluation and correction of psycho-emotional state of such patients. The lack of clearly developed approaches for correction to dental intervention, directly affects the quality of their dental care. The peculiarities of the management of patients suffering from arterial hypertension.